A Flexible Quasi‐Solid‐State Nickel–Zinc Battery with High Energy and Power Densities Based on 3D Electrode Design. Issue 39 (26th August 2016) - Liu, Jinping; Guan, Cao; Zhou, Cheng; Fan, Zhen; Ke, Qingqing; Zhang, Guozhen; Liu, Chang; Wang, John
Abstract : A flexible quasi‐solid‐state Ni‐Zn battery is developed by using tiny ZnO nanoparticles and porous ultrathin NiO nanoflakes conformally deposited on hierar chical carbon‐cloth–carbon‐fiber (CC‐CF) as the anode (CC‐CF@ZnO) and cathode (CC‐CF@NiO), respectively. The device is able to deliver high performance (absence of Zn dendrite), superior to previous reports on aqueous Ni–Zn batteries and other flexible electrochemical energy‐storage devices.